Pengamanan Aset Berupa Tanah Milik Pemerintah Kabupaten Seruyan - Sarifudin; Novianto Eko Wibowo (Restorica: Jurnal Ilmiah Ilmu Administrasi Negara dan Ilmu Komunikasi, 2025)
The security of assets in the form of land belonging to the Seruyan Regency Government has been implemented. Badan Keuangan dan Aset Daerah (BKAD) Seruyan Regency is making efforts to ensure that land assets remain in the control of the Seruyan Regency Government and prevent land assets from being confiscated by other parties. However, in its implementation there are still obstacles and problems faced. This research aims to find out how the Seruyan Regency Government attempts to safeguard its land assets. The research method used in this research is a descriptive method with a qualitative approach. The data collection methods used were observation, interviews and documentation. Data analysis in this research is reduction, presentation and drawing conclusions. The technique for testing the validity of the data in this research is to use source triangulation techniques and data collection technique triangulation. From the research results, the security of assets in the form of land belonging to the Seruyan Regency Government which has been implemented is still not optimal, such as administrative security which is still less than optimal, such as differences between recording data and real conditions in the field, a lot of land has not yet installed fences, boundary markers or land ownership signs. , and there is still a lot of land that does not yet have legal proof of ownership documents or certificates. Based on these problems, researchers provide suggestions for the Seruyan Regency Government to maximize efforts to safeguard assets in the form of land, especially in terms of legal security, so that SKPD as property users play an active role in the land certification stage.